The crisis of social market economy in the context of globalisation processes - Dylus, Aniela (Annales. Etyka w Życiu Gospodarczym, 2019)
In the context of globalisation processes, the social market economy (SME) is in crisis. A reflection on the features of this model is closely related to the scientific dispute over its designation. It could be perceived as a theory, a political programme, a sort of economic order, a structure, a model or a system of economic and social development. Sometimes it is perceived as an idealistic vision or even a political utopia (Niklas Luhmann). Others (e.g.: Peter Koslowski) argue that this system has come to an end. To support this thesis, they refer to various arguments: a lack of consensus on redistribution, a demographic crisis, the depletion of solidarity resources, an intergenerational imbalance that threatens retirement systems and many others. Despite the range of these arguments, it appears that the SME still has a certain potential that could be freed. Combating difficulties associated with globalisation processes, such as the dominance of the economy over politics, ‘tax starvation’ of the welfare state, marginalisation of trade unions, dispersion of ownership and its detachment from responsibility, “financialisation” of economy, or dominance of ‘casino capitalism’, could help to heal the SME. The crisis in financial markets might be paradoxically an opportunity to return to the ethical foundations of the SME.